Rancang Bangun Prototype Alat Pembersih Runway Pada Bandar Udara Ds Dengan Model Kano Dan Metode Quality Function Deployment (QFD) - Wahyudien, Mohammad Arief Nur; Masniar, Masniar; Hahury, Sanny; putra, kusuma (Metode : Jurnal Teknik Industri, 2023)
Based on observations and interviews with Bangland Airport unit officers kp still uses manual methods to clean the runway. This causes officers to experience difficulties in cleaning the runway.From these problems the researcher’s goal is to design a runway cleaning tool that suits consumer needs through the Kano model approach and the QFD method. Kano model approach is used to classify the attributes of consumer needs into 4 categories. The processing results of the Kano method show that there are no attributes that fall into the attractive category, where out of 10 statements 7 statements fall into the One-dimensional category, 3 statements fall into the Must-be category and 1 falls into Indifferent. While processing the Quality Function Deployment (QFD) and House of Quality (HOQ) methods translates consumer needs in the form of technical characteristics and is developed into target specifications and calculation analysis to obtain priority order for product design. The QFD and HOQ results show that the attribute that gets the first priority is the runway cleaning tool which has distributor sweepers and guide sweepers with an absolute important value of 153.06. The results of all calculations are made in a design and realized in the form of a prototype.